Representation of Saibatin Nampan Fabric as a Form of Woven Artisanal Preservation in Lampung - Anjar Nur Cholifah; Susi Susyanti (Institut Seni Indonesia Surakarta, 2026)
The Nampan fabric is a traditional cultural artifact produced through weaving techniques by the Saibatin Tribe along the coast of Lampung. This fabric features various sizes, colors, and square-shaped patterns. However, information regarding Nampan fabric remains limited, and previous studies have not comprehensively mapped the empirical data gaps regarding its visual taxonomy. This study aims to visualize data on the shapes, patterns, and sizes of Nampan fabric, record the frequency of each motif's appearance, and analyze its functionality. A total of 83 Nampan fabrics were documented and classified based on their specific characteristics. As a long-term preservation effort, this research includes converting images from physical/raster format to vector format to generate precise digital asset standardization. This study employs a qualitative method with data visualization analysis techniques, utilizing source and method triangulation through field observations, interviews with cultural curators (pamong budaya), and museum catalog studies. The results indicate a contrast dominance of general patterns with 42 findings, followed by 24 ship patterns, 14 fauna patterns, and only 3 flora patterns. The dominance of general patterns represents the high utility of this fabric for dynamic daily functional needs. The average dimensions of Nampan fabric are 59.48 cm in length and 56.42 cm in width, which are practically designed as food covers or table mats. Through a collaborative digitalization approach, it is hoped that Nampan fabric can maintain its value as a significant cultural heritage in Indonesia and gain international recognition.